Isotopic Equilibration in Convective Downdrafts. Issue 15 (9th August 2022) - Torri, Giuseppe
Abstract: While it is becoming increasingly clear that stable water isotopologues are important tools in the study of atmospheric convection, many questions remain on how different processes affect them. This work is focused on water vapor isotopes in precipitation‐driven downdrafts. Using idealized simulations, the contributions of rain evaporation and liquid‐vapor equilibration processes are analyzed. It is shown that rain evaporation tends to deplete water vapor isotopes throughout the downdraft's descent, whereas equilibration has a neutral or depleting effect in the first half of the downdraft's life cycle and an enriching one in the second half. The total contribution of the two processes is then discussed, and it is argued that equilibration has an overall small effect compared to rain evaporation. Finally, using two sensitivity experiments, it is shown that the role played by equilibration varies significantly in regimes with different concentrations of cloud condensation nuclei. Plain Language Summary: Water naturally exists in various forms which differ only by their mass. These small discrepancies provide water molecules with slightly different physical properties. This fact might be used to gain important information about the history of water vapor molecules in an air parcel. This study focuses on descending air currents that occur in storms and aims at clarifying how two microscopic processes might affect water molecules of various masses differently. The first process is the evaporation of rain, which takes place below clouds when water molecules flow from the liquid to the vapor phase. The other process, known as equilibration, is an exchange of heavier water molecules between the liquid and the vapor that takes place below clouds even without rain evaporation. The results discussed here could help interpret computer model simulations and observational data of convective storms. Key Points: Equilibration has a neutral or depleting effect in the first stages of the downdraft, and an enriching effect later The overall contribution of equilibration is smaller than that of evaporation Equilibration might play a greater role when the concentration of cloud condensation nuclei is lower